Pia Guldager Bilde – Mark L. Lawall (eds.), Pottery, Peoples and Places. Study and Interpretation of Late Hellenistic Pottery, BSS 16 - Warner Slane, Kathleen (Journal of Hellenistic Pottery and Material Culture, 2020)
The papers in this volume are about half of those delivered at a conference in November 2008, sponsored by the Danish National Research Foundation’s Centre for Black Sea Studies. The conference focused on ceramics in the eastern Mediterranean and Pontic regions in the 2nd century BCE, and the event coincided with the finalization of the manuscript on the lower city of Olbia Pontike, an area of the city that suffered a significant decline in the later 2nd century BCE. The range of topics is very well chosen, illuminating both the sources of imports and their consumption on major Black Sea sites. Several of the papers include bibliography as late as 2011.